2007
DOI: 10.1007/s11146-007-9061-7
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Market for Corporate Control Function for Property Companies?

Abstract: We investigate 95 takeovers of property companies all over the world and find that only two of those are hostile. To determine the effectiveness of the market for corporate control, we first study characteristics of targets and acquirers compared to a control sample, using the complete global universe of listed property companies during the most recent takeover wave (1999)(2000)(2001)(2002)(2003)(2004). We find that the inefficient management hypothesis holds for both REITs and non-REITs, as targets exhibit si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 65 publications
15
53
0
Order By: Relevance
“…In addition, the result supports the argument by Eichholtz and Kok (2008) that, due to their regulatory environment, REITs may be less vulnerable to agency problems. Our results are consistent with prior REIT research by Sahin (2005) who observed insignificant BHARs of +3.56% over the three-year event period.…”
Section: Bhar Resultssupporting
confidence: 78%
“…In addition, the result supports the argument by Eichholtz and Kok (2008) that, due to their regulatory environment, REITs may be less vulnerable to agency problems. Our results are consistent with prior REIT research by Sahin (2005) who observed insignificant BHARs of +3.56% over the three-year event period.…”
Section: Bhar Resultssupporting
confidence: 78%
“…There is compelling evidence that the takeover market is ineffective in the REIT sector. For instance, Campbell et al (2005) and Eicholtz and Kok (2008) establish that hostile takeovers are virtually non-existent among REITs. These authors and several others argue that the special regulatory provisions of REITs with respect to dividend distribution, asset structure and ownership composition make it difficult to launch hostile takeovers against REITs.…”
Section: Anti-takeover Provisionsmentioning
confidence: 99%
“…Several authors have documented that hostile takeovers are non-existent among REITs (Campbell et al (2001), Eicholtz and Kok (2008)). This implies that, in general, REIT managers face no serious takeover threat.…”
Section: Anti-takeover Provisionsmentioning
confidence: 99%
See 2 more Smart Citations